CONDITONS LEGALES DES FEMMES ALLAITANTES EN DETENTION EN REPUBLIQUE DEMOCRATIQUE DU CONGO : CAS DE LA PRISON CENTRALE DE KISANGANI - Salumu, Fiston WANDJA; Ludovic MBAYA NSOBA,; Ibrahim KATHY MBIYE,; Samy KATUSI KOLUWA,; Jolie KAVIRA KITWANDUMBA,; KAPITENI ALOISI Négro, (IJRDO - Journal of Social Science and Humanities Research, 2019)
The situation of the detention of prisoners in the prisons and dungeons of the Democratic Republic of Congo in general and the city of Kisangani in particular presents a very alarming diagnosis as to the respect of the national and international standards, concerning the conditions of detention of the persons incarcerated.               Today, it can be observed that the conditions of detention in prison houses remain unacceptable, characterized by serious deficiencies due, among other things, to food, hygiene and health care, thus transforming some prisons into real ones. hospices.Indeed, the Congolese State no longer offers adequate medical care to the detainees. State nurses and doctors are sometimes still in place in these places, but they lack the appropriate drugs to such a degree that the majority of the detainees are in a bad state of health, because struck by the malnutrition resulting consequently ravages mortals.               Overcrowding is the rule in prisons and dungeons in the DRC because a large number of prisons have fallen into disrepair and can only use part of their infrastructure.And among these detainees are lactating women related to their children.How does the Congolese State regulate the cases of this category of detainees?               From the review of this article, it will be discovered that no specific legal provisions relating to the detention of breastfeeding women are currently taken in the DRC. And in this situation, the recommendation consists of the application of international legal instruments, ratified by the DRC as described in this article.